2021
DOI: 10.3390/agronomy11061112
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Social Barriers of Precision Farming in Hungary

Abstract: Precision farming may play an important role in agricultural innovation. The study focuses on the attitude of Hungarian farmers toward precision farming. Based on the relevant technical literature, we performed a nationally representative questionnaire survey of 594 farmers and deep interviews with experts and farmers (30 persons). As regards the questionnaire, the authors found that the management of the average farm size in Hungary has the highest willingness to innovate and the second highest level of educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 53 publications
(53 reference statements)
1
18
0
Order By: Relevance
“…A survey pointed out that two-thirds of Hungarian farmers indicated that they use at least one of the 10 listed precision technologies, which shows the high level of uncertainty that is inherent in the interpretation of PF. Balogh et al (2021) [14] examined Hungarian farmers' very differential interpretations of PF.…”
Section: Introductionmentioning
confidence: 99%
“…A survey pointed out that two-thirds of Hungarian farmers indicated that they use at least one of the 10 listed precision technologies, which shows the high level of uncertainty that is inherent in the interpretation of PF. Balogh et al (2021) [14] examined Hungarian farmers' very differential interpretations of PF.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid this problem, the use of fertilizers and pesticides has been called for, but this method involves the use of finite and unsustainable resources [52][53][54]. With this in mind, scientists have begun to place greater emphasis on sustainability and increasing the resilience of crops to climate change [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…Farmers may be resistant to change and may prefer traditional methods that have been used for generations. Furthermore, a lack of awareness and understanding of PA techniques can be a significant social barrier (Balogh et al., 2021). There is a need for training and educational programs that provide farmers with the knowledge and skills required to implement sustainable PA practices effectively (Balogh et al., 2021; Lencsés et al., 2014).…”
Section: Barriers and Challenges To Implementing Sustainable Precisio...mentioning
confidence: 99%